Molecular Identification of Mycobacterium Tuberculosis in the Milwaukee County Institution Grounds Cemetery - (:unkn) unknown (My University, 2015)
The possibility of identifying Mycobacterium tuberculosis in skeletal remains has been a debated topic for many years. This study utilizes the remains from the 1991 and 1992 excavations of the Milwaukee County Institution Grounds Cemetery, a collection of human skeletons ranging from 1882 to 1925, of various ages and sexes, to address that possibility. To test the utility of previously used methods of osteological identification of tuberculosis, the collection has been analyzed for the IS6110 repetitive element marker using molecular biological techniques, such as Polymerase Chain Reaction (PCR). Eighty-six skeletons from the collection have been analyzed, with nine of them showing evidence of skeletal tuberculosis. PCR has also been carried out with the oxyR marker to rule out Mycobacterium bovis contamination on all positive IS6110 samples. The goal of the study was to evaluate whether or not osteological identification of M. tuberculosis is possible and whether it can be confirmed using molecular biological techniques.
Keywords: Historic Archaeology; IS6110; Milwaukee; Osteology; Tuberculosis